KEWAJIBAN DAN TANGGUNG JAWAB DIREKSI DALAM RANGKA PENYESUAIAN ANGGARAN DASAR PERSEROAN DENGAN PERKEMBANGAN PENGATURAN PERSEROAN TERBATAS DI INDONESIA - Hendro Saptono, Maridza Puspitasari, Herman Susetyo, (Diponegoro Law Journal, 2012)
In the last few years, doing business by establishing Limited Liability Company (LLC) or called  Limited Company, become the most favourite and prevalent model because of its limited responsibility,          moreover               Limited             Company    also          gives           easiness          to              owner (Shareholders) to switch off its company (to everyone) by selling all of the shares they have to the company. In every Limited Company, there is an Articles of Association which is a set of the rules that  becomes the foundation of organization and the working of Limited Company according to law. Formerly, Limited Liability Company in Indonesia was established by Kitab Undang-Undang Hukum Dagang or Law  Number 1 Year 1995 regarding Limited Liability Company until  the existence of  Law  Number 40 Year  2007  regarding  Limited  Liability Company. Therefore, Limited Liability Companies need to adjust their Articles of Association in one year. If the adjustment is neglected, the Limited Liability Company could be dismissed by court decree on request of Attorney or intended party. This research's goals are to go deep into and analyze about the regulation of Director's responsibility  in order to the adjustment of Limited Company's Articles of Association in terms of Kitab Undang-Undang Hukum Dagang, Law Number 1 Year 1995 regarding Limited Liability Company, and Law Number 40 Year  2007 regarding Limited Liability Company with the legal consequences if Director doesn't implement fiduciary duty principal to Limited Company. The approach method that be used in this research is juridical-normative approach method, by  using  secondary data which has been collected through library research which includes primary, secondary,  and tertiary legal materials. Specification of the research is descriptive-analytical, while the data analysis has been done qualitatively by using deductive- inductive method. From the result of this research which has been conducted by the author, obtained a result or conclusion based on Article 97 Law Number 40 Year 2007 that Director takes a full responsibility personally if the adjusment of Articles of Association to Law Number 40 Year 2007 has not been done due to the negligence of Director thus making dismissal of Limited Company by court decree, and the legal consequences if Director doesn't implement fiduciary duty principal to Limited Company are Director takes a full responsibility personally, jointly, and Director can be sued by Shareholders who represents at least 1/10 (one-tenth) part from the amounts of all shares with voting rights, and also by another Board of Directors, and part of Board of Commissioners in the name of Limited Company by filing the claim to District Court.